Traits of Patients With Pituitary Tumors in Multiple Endocrine Neoplasia Type 1 and Comparing Different Mutation Status - Lin, Kuan-Yu; Kuo, Yu-Ting; Cheng, Mei-Fang; Chen, Pei-Lung; Wang, Hsiu-Po; Cheng, Tsu-Yao; Chang, Chia-Hsuin; Kao, Hsiang-Fong; Yang, Shih-Hung; Li, Hung-Yuan; Lin, Chia-Hung; Chou, Yuh-Tsyr; et al. (The journal of clinical endocrinology and metabolism, 2023)
Abstract Context Recent studies suggest that the clinical characteristics and biological behavior of pituitary tumors (PITs) in patients with multiple endocrine neoplasia type 1 (MEN1) may not be as aggressive as previously reported. Increased imaging of the pituitary as recommended by screening guidelines identifies more tumors, potentially at an earlier stage. However, it is unknown if these tumors have different clinical characteristics in different MEN1 mutations. Objective To assess characteristics of patients with MEN1 with and without PITs, and compare among different MEN1 mutations. Methods Data of patients with MEN1 in a tertiary referral center from 2010 to 2023 were retrospectively analyzed. Results Forty-two patients with MEN1 were included. Twenty-four patients had PITs, 3 of which were invasive and managed with transsphenoidal surgery. One PIT enlarged during follow-up. Patients with PITs had a higher median age at MEN1 diagnosis than those without PITs. MEN1 mutations were identified in 57.1% of patients, including 5 novel mutations. In patients with PITs, those with MEN1 mutations (mutation+/PIT+ group) had more additional MEN1-associated tumors than those without (mutation−/PIT+ group). The mutation+/PIT+ group had a higher incidence of adrenal tumors and a lower median age at initial manifestation of MEN1 than the mutation−/PIT+ group. The most common neuroendocrine neoplasm was nonfunctional in the mutation+/PIT+ group and insulin-secreting in the mutation−/PIT+ group. Conclusion This is the first study comparing characteristics of patients with MEN1 with and without PITs harboring different mutations. Patients without MEN1 mutations tended to have less organ involvement and it might be reasonable for them to receive less intensive follow-up.